2022
DOI: 10.3390/ijms23105300
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylceramide Changes Bacterial Metabolism and Increases Gram-Positive Bacteria through Tolerance to Secondary Bile Acids In Vitro

Abstract: Glucosylceramide is present in many foods, such as crops and fermented foods. Most glucosylceramides are not degraded or absorbed in the small intestine and pass through the large intestine. Glucosylceramide exerts versatile effects on colon tumorigenesis, skin moisture, cholesterol metabolism and improvement of intestinal microbes in vivo. However, the mechanism of action has not yet been fully elucidated. To gain insight into the effect of glucosylceramide on intestinal microbes, glucosylceramide was anaerob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…There was a significant increase in the abundance of Acetobacter and Lactobacillus , the commonest genera in the fly gut [ 62 ]. A recent study has demonstrated that GluCer positively regulates growth of certain bacterial species [ 63 ], so GluCer deposition in intestinal cells of the gut lumen may trigger a shift in bacterial number and composition.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant increase in the abundance of Acetobacter and Lactobacillus , the commonest genera in the fly gut [ 62 ]. A recent study has demonstrated that GluCer positively regulates growth of certain bacterial species [ 63 ], so GluCer deposition in intestinal cells of the gut lumen may trigger a shift in bacterial number and composition.…”
Section: Discussionmentioning
confidence: 99%
“…Life 2024, 14, 739 9 of 12 In summary, this study provides new insights into the role of glucosylceramide in the colon by decreasing fecal hardness. Given that glucosylceramide increases the tolerance of intestinal bacteria to secondary bile acids and promotes the production of lactic acid by intestinal bacteria [34], a new hypothesis regarding the role of glucosylceramide was considered (Figure 4). In summary, this study provides new insights into the role of glucosylceramide in the colon by decreasing fecal hardness.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Dietary glucosylceramide has been reported to prevent colon preneoplastic lesions [ 21 ], prevent head and neck cancers [ 22 , 23 ], inhibit colorectal cancer [ 24 ], inhibit throat cancer [ 25 ], inhibit inflammatory bowel disease (IBD) [ 26 , 27 , 28 ], improve atopic dermatitis, maintain skin moisture [ 29 ], improve lipid metabolism [ 26 , 30 ], improve cholesterol metabolism [ 31 ], improve intestinal microbial flora [ 32 , 33 ], and relieve bile acid pressure [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, probiotics are able to inhibit tumor angiogenesis, resist ecological dysregulation, promote the establishment of non-inflammatory bacteria, change the composition of a dysregulated microbiome, and reduce liver inflammation and the development of HCC [ 125 ]. Studies have shown that the removal of Gram-positive bacteria by antibiotic treatment with vancomycin—including bacteria that mediate primary-to-secondary bile acid conversion—is sufficient to induce hepatic NKT cell accumulation and reduce liver tumor growth [ 123 , 126 ]. Feeding secondary bile acids or colonization with bile-acid-metabolizing bacteria reverses NKT cell accumulation and liver tumor growth inhibition in mice with altered gut commensal bacteria.…”
Section: Interaction Between Intestinal Flora and Bile Acidsmentioning
confidence: 99%